Artificial Intelligence Regulation on Labour Market: Comparative Perspectives on the European Union Artificial Intelligence Act in the Indonesian Context - Rofi Aulia Rahman (Universitas Negeri Semarang, 2024)
Advances in artificial intelligence technology (AI) have created new challenges for the legal framework in the field of labour law. The approval of the European Union (EI) AI Act in March13th, 2024, aimed at ensuring the safety and ethical use of AI systems in the EU, has made a significant step forward in regulating AI. This article explains the development of law-making process of the EU AI Act and finds a connection between the EU AI Act and labour market which that law might be the grand design to regulate many aspects of labour side. It then critically evaluates the development of law in Indonesia which is far for expectation to regulate AI within its legal system. Although the challenges and constraints of AI in the labour market have already occurred and are being felt, the task of building up the right legal framework for the needs of workers in the labour market is already at hand. Finally, this paper underlines the importance of comprehensive regulation of AI within legal system for ensuring business climate, employment, data privacy, transparency, ethics, and accountability. However, AI Act in Indonesia remains vague, especially in the labour market sector, and does not regulate AI in its legal system. Therefore, AI Act is necessary for Indonesia to overcome current and future challenges on labour market.